JNK signaling coordinates with ecdysone signaling to promote pruning of Drosophila sensory neuron dendrites - Zhu, Sijun; Chen, Rui; Soba, Peter; Jan, Yuh-Nung (Development, 2019)
Developmental pruning of axons and dendrites is crucial for the formation of precise neuronal connections, but the mechanisms underlying developmental pruning are not fully understood. Here, we have investigated the function of JNKsignaling in dendrite pruning using Drosophila class IV dendritic arborization (c4da) neurons as a model. We findthat lossof JNKor its canonical downstreameffectors Jun orFos led to dendrite-pruning defects in c4da neurons. Interestingly, our data show that JNK activity in c4da neurons remains constant from larval to pupal stages but the expression of Fos is specifically activated by ecdysone receptor B1 (EcRB1) at early pupal stages, suggesting that ecdysone signaling provides temporal control of the regulation of dendrite pruning by JNK signaling. Thus, our work not only identifies a novel pathway involved in dendrite pruning and a new downstream target of EcRB1 in c4da neurons, but also reveals that JNK and Ecdysone signaling coordinate to promote dendrite pruning.
CRIS-Team Scopus Importer:2021-11-16
Keywords: Dendrite pruning; Drosophila; Ecdysone; Jnk; Sensory neurons; Wnt5